PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI, INFORMASI, DAN KOMUNIKASI DALAM MENINGKATKAN HASIL BELAJAR SUBTEMA LINGKUNGAN TEMPAT TINGGALKU - Entis Sutisna; Lina Novita; M. Iqbal Iskandar (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2020)
This study uses quantitative design with Quasi Experiment. This study is aimed at improving students achievement subtheme my surrounding through the use of information and technology based media. Sample of this study are fourth grade students from class A and C in Sekolah Dasar Negeri Cimahpar 1 comprise of 65 students. This research was conducted in even semester of academic year 2018/2019. Analysis technique used in this research is data analysis prerequisite test which include galat normality test, homogeneity variance test, then hypothesis test is done using t test. Based on the result of data analysis N-Gain score for students achievement using information and technology based media is 80,8 and students mastery result is 96,9 percent. On the other hands learning using conventional media the N-Gain score is 70,2 and students mastery result is 84,8 percent. The result of hypothesis testing shows that is rejected and is accepted because tvalue (3,39915) greater than ttable (1,99834). Based on the research above it can be concluded that there is a difference result between students achievement on subtheme my surrounding through the use of information technology based media and conventional media. Therefore it can be said that the use of information technology based media is effective for learning. It means that students have interest in learning, active in discussion, and motivated in doing classroom activity.